THE USE OF STORY-TELLING METHOD TO IMPROVE STUDENTS’ SOCIAL-CARE CHARACTER IN LEARNING SOCIAL STUDIES (Classroom Action Research in class VII G of SMP Negeri 3 Lembang) - Pratama, Dia Widiana (International Journal Pedagogy of Social Studies, 2018)
ABSTRACT This research is motivated by the problems that researcher found at the time of preliminary observation in class VII G of SMP Negeri 3 Lembang. Based on the observation, researcher found problems such as lack of learners’ social-care character in learning Social Studies. This is evidenced by several problem indicators including the attitude of students, this was shown by their indifference towards a sick friend; students’ habit of choosing group members based on the proximity in a particular group, if the group was not formed based on the students’ interests, the students can not cooperate well with each other; then the students’ low tolerance, as shown by the frequent occurrence of noise in the classroom, due to the students’ difficulty in accepting other students’ different opinion, that ensued bullying between friends by mocking and laughing. The alternative solution to the problem chose by the researcher is to apply the story-telling method, in which the teacher tells a story to arise students’ social-care character by emulating the good parts in the story.Keywords: Social-Care Character, Story-telling methods, Social Studies Learning